2022
DOI: 10.1136/heartjnl-2021-320708
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): a risk factor for atherosclerosis and an emerging therapeutic target

Abstract: Lipoprotein(a) (Lp(a)) is a complex circulating lipoprotein, and increasing evidence has demonstrated its role as a risk factor for atherosclerotic cardiovascular disease (ASCVD) and as a possible therapeutic target. Lp(a) atherogenic effects are attributed to several potential mechanisms in addition to cholesterol accumulation in the arterial wall, including proinflammatory effects mainly mediated by oxidised phospholipids. Several studies have found a causal and independent relationship between Lp(a) levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 54 publications
1
45
1
Order By: Relevance
“…Cardiac rehabilitation programs in obese patients also improve exercise tolerance and functional capacity. Recent studies [ 30 , 39 , 40 , 41 ] have confirmed past results [ 42 , 43 , 44 , 45 , 46 ], but further studies are needed to better characterize the beneficial effects in obese patients, both with and without CV disease [ 47 ]. Gondoni et al [ 39 ] studied 772 obese patients aged ≥70 years with BMI at baseline of 37.6 ± 4.4 kg/m 2 and coronary artery disease (prior myocardial infarction, coronary angioplasty, or coronary artery bypass surgery) and/or heart failure.…”
Section: Cardiac Rehabilitationmentioning
confidence: 83%
“…Cardiac rehabilitation programs in obese patients also improve exercise tolerance and functional capacity. Recent studies [ 30 , 39 , 40 , 41 ] have confirmed past results [ 42 , 43 , 44 , 45 , 46 ], but further studies are needed to better characterize the beneficial effects in obese patients, both with and without CV disease [ 47 ]. Gondoni et al [ 39 ] studied 772 obese patients aged ≥70 years with BMI at baseline of 37.6 ± 4.4 kg/m 2 and coronary artery disease (prior myocardial infarction, coronary angioplasty, or coronary artery bypass surgery) and/or heart failure.…”
Section: Cardiac Rehabilitationmentioning
confidence: 83%
“…Higher level of CumLp(a) exposure and impaired glucose metabolism exert their joint pathogenic effect on long-term adverse cardiovascular outcomes through multiple potential mechanisms including atherogenesis, vascular inflammation, and thrombosis. 1 , 21 On the one hand, Lp(a) has its atherogenic effect associated with its LDL-like composition which leads to the development and vulnerability of atherosclerotic plaques. Furthermore, Lp(a) possesses unique features secondary to its component of apo(a), that is thought to have relatively prothrombotic property because of its structural homology with plasminogen.…”
Section: Discussionmentioning
confidence: 99%
“… 23 In addition, Lp(a)’s components are believed to attach to fibrin to form the prothrombotic complex that inhibits plasminogen activation and fibrinolysis, thus promoting thrombus formation. 21 On the other hand, chronic mild inflammation is a recognized pathological mechanism of diabetes and prediabetes. Overall effects may eventually promote plaque rupture, leading to adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative therapeutic approaches based on gene silencing technologies represent a new opportunity to manage CVD risk due to dyslipidemia [11]. This new therapeutic strategy uses antisense oligonucleotides (ASOs) or small interfering RNAs (siRNAs) for silencing gene expression.…”
mentioning
confidence: 99%